Nonuniform distribution and spectral tuning of photosensitive retinal ganglion cells of the mouse retina. - Hughes, S; Watson, T; Foster, R; Peirson, SN; Hankins, M (2013)
Melanopsin-expressing photosensitive retinal ganglion cells (pRGCs) represent a third class of retinal photoreceptor. These cells are intrinsically photosensitive, but also receive inputs from rod and cone photoreceptors, acting as the primary sensory conduit mediating non-image-forming responses to light. Multiple subtypes of pRGC have been described in the mouse retina with characteristic morphologies and functional properties, and which perform distinct physiological roles. Here, we examine the levels of melanopsin expression and distribution of pRGC subtypes across the mouse retina, identifying a previously unreported anatomical and functional specialization of the melanopsin system. Our results show a dorsal-ventral gradient in the expression of melanopsin and the distribution of pRGCs, which, combined with dorsal-ventral gradients in ultraviolet-sensitive and medium-wavelength-sensitive cone opsin expression, produce dramatic variations in the ratio of cone opsins and pRGCs across the retina. Using c-fos expression as a marker of light activation in vivo, we show that the responses of pRGCs are spectrally tuned by gradients in cone opsin expression depending on their location in the retina. These data illustrate the importance of classical photoreceptors in providing spectral tuning of pRGC light responses and have important implications for the complexity of non-image-forming responses to light.